The Effectiveness of Preoperative Exercises on the Outcomes After Anterior Cruciate Ligament Reconstruction: A Systematic Review - Ali Yalfani; Ahmad Ebrahimi Atri; Maedeh Taghizadeh Kermani (Biyumikānīk-i varzishī)
Objective: Quadriceps weakness is common after Anterior Cruciate Ligament (ACL) injury and subsequent surgery. Preoperative defects affect postoperative outcomes. The purpose of this review study was to investigate whether preoperative exercises can affect the postoperative outcomes after ACL reconstruction. Methods: The searching for papers was conducted in the PubMed database among the studies from 1990 to 2019 using following keywords: ACL preoperative exercise, prehabilitation ACL, and preoperative protocol. The initial search yielded 442 papers. Then, based on the inclusion and exclusion criteria, 10 papers were selected for the final review. Methodological quality of the studies was assessed by using the Physiotherapy Evidence Database (PEDro) scale and the Critical Appraisal Skills Program (CASP). Results: Some preoperative exercises (traditional, strength, and neuromuscular) can significantly increase the knee extensor strength and knee function in men and women after surgery in the short and long periods. The mean PEDro score for 8 randomized controlled trials was 6, indicating their moderate methodological quality. Moreover, the CASP score for 2 cohort studies was 10 and 11 out of 12. Conclusion: Preoperative rehabilitation consisting of neuromuscular and strength exercises followed by a criterion-based postoperative rehabilitation program cause greater functional outcomes and faster recovery of the knee extensor strength after ACL reconstruction. Preoperative rehabilitation should be considered as a standard treatment to maximize functional outcomes after ACL reconstruction.